Improving Unsustainable Environmental Governance in South Africa: the Case for Holistic Governance - LJ Kotze (Potchefstroom Electronic Law Journal, 2006)
Environmental law in South Africa has developed in a rapid fashion since the inception of the new constitutional dispensation in 1994. This development is evident from, inter alia, the constitutionalisation of the environmental right in section 24 of the Constitution of the Republic of South Africa, 1996. Section 24 contains amongst other provisions, directive principles that impose duties on government to protect the environment for present and future generations through reasonable legislative and other measures. It is apparent from section 24 that these measures should ensure environmental governance practices that are aimed at the achievement of sustainable results. The South African environmental governance regime is, however, characterised by fragmentation that may negate the achievement of sustainable environmental governance. It is argued in this article that, for environmental governance to become sustainable, it is necessary to integrate environmental governance efforts, possibly by way of a holistic approach to environmental governance. In light of the above, this article: investigates the nature and extent of fragmentation; explores reasons for fragmentation; discusses disadvantages of fragmented governance efforts in South Africa; investigates the concept of integration and holistic governance as means to achieve sustainable environmental governance results; and makes recommendations regarding the eventual achievement of integrated, holistic and sustainable environmental governance.